Responding to Aid Volatility : Government Spending on District Health Care in Zambia 2006-2017 - Jackson, Amy (Taylor and Francis, 2021)
A corruption event in 2009 led to changes in how donors supported the Zambian health system. Donor funding was withdrawn from the district basket mechanism, originally designed to pool donor and government financing for primary care. The withdrawal of these funds from the pooled financing mechanism raised questions from Government and donors regarding the impact on primary care financing during this period of aid volatility. Financial data were extracted from Government documents and adjusted for inflation. Budget and expenditure for the district level over the period 2006 to 2017 were disaggregated by programmatic area for analysis. Despite the withdrawal of donor funding from the district basket after 2009, funding for primary care allocated to the district level more than doubled from 2006 to 2017. However, human resources accounted for this increase. The operational grant, on the other hand, declined.